Triptolide mitigates the inhibition of osteogenesis induced by TNF-α in human periodontal ligament stem cells via the p-IκBα/NF-κB signaling pathway: an in-vitro study - Hao Chen; Lina Zhang; Simeng Du; Daiwei Yang; Xiaobin Cui; Huadong Zhao; Jun Zhang (BMC, 2024)
Abstract Background Triptolide is a widely utilized natural anti-inflammatory drug in clinical practice. Aim of this study was to evaluate effects of triptolide on hPDLSCs osteogenesis in an inflammatory setting and to investigate underlying mechanisms. Methods Using the tissue block method to obtain hPDLSCs from extracted premolar or third molar. Flow cytometry, osteogenic and adipogenic induction were carried out in order to characterise the features of the cells acquired. hPDLSC proliferative activity was assessed by CCK-8 assay to determine the effect of TNF-α and/or triptolide. The impact of triptolide on the osteogenic differentiation of hPDLSCs was investigated by ALP staining and quantification. Osteogenesis-associated genes and proteins expression level were assessed through PCR and Western blotting assay. Finally, BAY-117,082 was used to study the NF-κB pathway. Results In the group treated with TNF-α, there was an elevation in inflammation levels while osteogenic ability and the expression of both osteogenesis-associated genes and proteins decreased. In the group co-treated with TNF-α and triptolide, inflammation levels were reduced and osteogenic ability as well as the expression of both osteogenesis-associated genes and proteins were enhanced. At the end of the experiment, both triptolide and BAY-117,082 exerted similar inhibitory effects on the NF-κB pathway. Conclusion The osteogenic inhibition of hPDLSCs by TNF-α can be alleviated through triptolide, with the involvement of the p-IκBα/NF-κB pathway in this mechanism.